The impact of digital skills on the mental health of rural residents: from the perspective of happiness - Zhou, Lei; Peng, Yubo; Xia, Qing (Frontiers in Psychology, 2025)
Happiness is one of the important manifestations of the psychological health of rural residents. Based on the data of the 2020 China Rural Revitalization Comprehensive Survey (CRRS), this paper constructs a theoretical analysis framework of “material compensation-emotional immersion” and adopts OLS model and instrumental variables method to study the influence of digital skills on the happiness of rural residents and the underlying mechanism. The regression results of the OLS model show that there is an “inverted U” curve relationship between digital skills and rural residents' happiness, which verifies the happiness effect of digital skills mastery, and also reveals that as the level of digital skills increases, it is easy to lead to distorted upward comparisons, fall into digital traps and form digital addiction, resulting in lower happiness. The mechanism analysis shows that the “inverted U” effect of digital skills on the happiness of rural residents is mainly transmitted through the material compensation effect, i.e., the objective income and subjective income satisfaction first rise and then fall. Although digital skills gradually build up a positive affective immersion effect, i.e., an increase in trust, it is not sufficient to offset the negative effect of the material compensation effect. Heterogeneity analysis shows that the happiness effect of digital skills is present in both low- and high-income farmer groups, reflecting the universality of the digital dividend. However, farmers at high income levels are more negatively affected, showing an “inverted U” type non-linear relationship, while farmers at low-income levels are only positively affected, showing a positive linear relationship. In addition, digital skills can reduce the welfare gap between rural residents with different levels of education. Accordingly, this paper provides empirical evidence on how to bridge the digital divide in the process of digital village construction in order to better improve the happiness of rural residents.